Kampus Merdeka dan Arah Pendidikan Republik Indonesia - Achmad Resa; Arum Asyfa Azahra; Muhammad Hasyim Romadani (Universitas Insan Budi Utomo, 2023)
This article aims to view the Kampus Merdeka program in a critical view. The Ministry of Education of Republic of Indonesia announced this program on 2020. This program tends to give more freedom for universities and students in their educational progress and purposes. One of the most important goals of this program is to graduate alumni who are ready to face the working field as the alumni of theuniversities nowadays do not link and match with the job demands. Despite the drawbacks of this concept, there are some benefits can be obtained from this program but with some criticism in it. This research is based on library research which analyses the relevant books and articles. It can be concluded that Kampus Merdeka is potential for developing multidiciplinary studies and maximizing the process oflearning in universities. It must be noted too that the main goal of education should not be neglected; it is to produce a good man. Only after fulfilling this main goal, the Kampus Merdeka program will benefit us more comprehensively.